2017
DOI: 10.1515/romneu-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Study of predisposing risk factors and etiology of chronic subdural hematoma in clipped patients of unruptured intracranial aneurysms – an institutional experience

Abstract: Abstract:Introduction: Chronic subdural hematoma in clipped patients of unruptured intracranial aneurysms might lead to sudden neurological deterioration and may need emergency evacuation. We studied the effects of various factors in its etiology. Materials and methods: A retrospective study of 91operated clipped patients of unruptured aneurysms in the year 2014-2015 was taken. Various predisposing factors were studied. Results: Goreisan use was not associated with any reduction in post operative CSDH formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that arachnoid plasty (ARP) with fibrin glue and gelatin sponge has been helpful in the prevention of postoperative CSDH via reducing subdural fluid collection. However, the effectiveness of ARP has not been fully validated [ 7 , 8 , 11 - 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that arachnoid plasty (ARP) with fibrin glue and gelatin sponge has been helpful in the prevention of postoperative CSDH via reducing subdural fluid collection. However, the effectiveness of ARP has not been fully validated [ 7 , 8 , 11 - 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%